The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/mc.23185
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling reveals the pivotal role of hrHPV driving copy number and gene expression alterations, including mRNA downregulation of TP53 and RB1 in penile cancer

Abstract: The incidence of penile cancer (PeCa) is increasing worldwide, however, the highest rates are reported in underdeveloped countries. The molecular mechanisms that underly the onset and progression of these tumors are still unclear. Therefore, our goal was to determine the genome-wide copy number alterations and the involvement of human papiloma virus (HPV) (TP53 and RB1), inflammatory (COX2 and EGFR), and PI3K/AKT pathway (AKT1, AKT2, EGFR, ERBB3, ERBB4, PIK3CA, and PTEN) associated genes in patients with PeCa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 69 publications
4
40
0
2
Order By: Relevance
“…In PSCC, Busso-Lopes et al [ 10 ] found that copy number variations (CNVs) of 19 genomic regions are commonly detected in HPV + tumors, including in chromosomal regions 2q33.2-q33.3 and 2q35. Macedo et al [ 13 ] also found several loci, such as 2p12-p11.2, 14q32.33, and 2p16.3, presented CNV in most of HPV+ PSCCs, and several CNVs were correlated with clinicopathological factors. However, none of these results could directly indicate whether these differences between HPV-positive and HPV-negative PSCCs were induced by virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PSCC, Busso-Lopes et al [ 10 ] found that copy number variations (CNVs) of 19 genomic regions are commonly detected in HPV + tumors, including in chromosomal regions 2q33.2-q33.3 and 2q35. Macedo et al [ 13 ] also found several loci, such as 2p12-p11.2, 14q32.33, and 2p16.3, presented CNV in most of HPV+ PSCCs, and several CNVs were correlated with clinicopathological factors. However, none of these results could directly indicate whether these differences between HPV-positive and HPV-negative PSCCs were induced by virus.…”
Section: Discussionmentioning
confidence: 99%
“…The integration pattern and characteristics of HPV in the PSCC genome are also unclear. Several studies have indicated that HPV-positive PSCC harbors a different genomic profile [ 10 , 11 , 12 , 13 ] and specific epigenetic alterations [ 12 ] when compared to HPV-negative PSCC or normal tissue. For instance, HPV-positive PSCC often harbors an APOBEC mutation [ 11 ]; copy number variations (CNVs) of 19 genomic regions are commonly detected in HPV-positive tumors [ 10 ]; HPV-positive tumors are characterized by the widespread loss of DNA methylation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that EGFR is often overexpressed its protein and gene dysregulation, has already been associated with advanced stage, lower overall survival and metastatic lymph node status (34). Downregulation of miR-145 may be one of the mechanisms for high expression of EGFR, especially in HPV positive tumors (35). Additionally, this microRNA can regulate pathways such as Wnt, TGF-beta, Calcium which are involved in cell growth, progression, survival, angiogenesis, and apoptosis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Macedo et al performed array-CGH in 20 of 55 PeSCC (81.8% of them were HPV positive) (19). D e s p i t e o f n o t h a v i n g a n y s i g n i f i c a n t c l i n i c a lhistopathological association, a noteworthy number of altered chromosomal regions coincided with sites of HPV integration into the human genome.…”
Section: Recurrent Cnasmentioning
confidence: 99%